Photodynamic therapy with Bixa orellana extract and LED for the reduction of halitosis: study protocol for a randomized, microbiological and clinical trial - Gonçalves, Marcela Leticia Leal (Trials, 2018)
BACKGROUND: Halitosis is an unpleasant breath odour that can interfere with the professional life, social life and quality of life of people who suffer from it. A modality of treatment that has been increasing in dentistry is antimicrobial photodynamic therapy (aPDT). Bixa orellana, popularly known as “urucum” is a plant native to Brazil. The seeds are used to produce a dye that is largely used in the food, textile, paint and cosmetic industries. The aim of this study is to verify whether aPDT with Bixa orellana extract and blue light-emitting diodes (LEDs) is effective in reducing halitosis. This method will also be compared with tongue scraping, the most commonly used conventional method for tongue coating removal, and the association of both methods will be evaluated. METHODS/DESIGN: A randomized clinical trial will be conducted at the dental clinic of the Universidade Nove de Julho. Thirty-nine patients will be divided by block randomization into three groups (n = 13) according to the treatment to be performed. In Group 1, tongue scraping will be performed by the same operator in all patients for analysis of the immediate results. Patients will also be instructed on how to use the scraper at home. Group 2 will be treated with aPDT with Bixa orellana extract and the LED light curing device: Valo Cordless Ultradent®. Six points in the tongue dorsum with a distance of 1 cm between them will be irradiated. The apparatus will be pre-calibrated at wavelength 395–480 nm for 20 s and 9.6 J per point. In Group 3, patients will be submitted to the tongue scraping procedure, as well as to the previously explained aPDT. Oral air collection with the Oral Chroma™ and microbiological collections of the tongue coating shall be done before, immediately after and 7 days after treatment for comparison. DISCUSSION: Halitosis treatment is a topic that still needs attention. The results of this trial could support decision-making by clinicians regarding aPDT using blue LEDs for treating halitosis on a daily basis, as most dentists already have this light source in their offices. TRIAL REGISTRATION: ClinicalTrials.gov, NCT03346460. Registered on 17 November 2017. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-018-2913-z) contains supplementary material, which is available to authorized users.